Synthesis, Characterization, and Functionalization of 1‐Boraphenalenes. (6th June 2018) - Kahan, Rachel J.; Crossley, Daniel L.; Cid, Jessica; Radcliffe, James E.; Ingleson, Michael J.
Abstract: 1‐Boraphenalenes have been synthesized by reaction of BBr3 with 1‐(aryl‐ethynyl)naphthalenes, 1‐ethynylnaphthalene, and 1‐(pent‐1‐yn‐1‐yl)naphthalene and they can be selectively functionalized at boron or carbon to form bench‐stable products. All of these 1‐boraphenalenes have LUMOs localized on the planar C12 B core that are closely comparable in character to isoelectronic phenalenyl cations. In contrast to the comparable LUMOs, the aromatic stabilization of the C5 B ring in 1‐boraphenalenes is dramatically lower than the C6 rings in phenalenyl cations. This is due to the occupied orbitals of π symmetry being less delocalised in the 1‐boraphenalenes.